Combinatorial drug approaches to tackle Candida albicans biofilms. Issue 8 (August 2015) - De Cremer, Kaat; Staes, Ines; Delattin, Nicolas; Cammue, Bruno PA; Thevissen, Karin; De Brucker, Katrijn
<x xml:space="preserve">Abstract</x> The human fungal opportunistic pathogen Candida albicans resides in the human gut, genitourinary tract and on the skin. The majority of infections caused by C. albicans are biofilm-related. In the first part of this review, we discuss new insights into C. albicans biofilm characteristics, concentrating on the extracellular matrix, phenotypic switching, efflux pumps and persister cells. It is widely accepted that this multicellular lifestyle is more resistant to traditional antifungal treatment compared to free-living cells. Therefore, much effort is put in the search for combinations of drugs leading to synergistic interactions against microbial biofilms to achieve lower effective doses of the drugs. In the second part of this manuscript, we review all recently identified compounds that act synergistically with azoles, echinocandins and/or polyenes against C. albicans biofilms.